Tax Cost of Investment Projects: the case of ICMS credits - Pessôa, Leonel Cesarino; da Silva, Marcello Muniz; Campanário, Milton de Abreu (Review of Business Management, 2011)
This article discusses the impact on the profitability of firms under Complementary Law 102/2000 (which abrogated the Law 89/96 – Kandir Law) allowing the appropriation of ICMS credits, due to investment in fixed assets goods, at a ratio of 1 / 48 per month. The paper seeks to demonstrate how this new system - which resulted in the transformation of the ICMS as a value added tax (VAT) consumption-type to an income-type - leads to a loss of approximately 30% of the value of credits to be recovered and the effect it generates on the cost of investment and the profits for small, medium and large firms. From the methodological point of view, it is a descriptive and quantitative research, which proceeded in three stages. Initially, we have obtained estimated value of net sales and volume of investments, based on report Painel de Competitividade prepared by the Federação das Indústrias do Estado de São Paulo (Fiesp/Serasa). Based on this information, it was possible to obtain estimates of the factors of generation of debits and credits for ICMS, using the model Credit Control of Fixed Assets (CIAP). Finally, we have calculated three indicators: (i) present value of debt recovery/value of credits, (ii) present value of debt recovery / investment value, (iii) present value of debt recovery / sales profitability. We have conclude that the system introduced by Complementary Law 102/2000 implicates great opportunity cost for firms and that legislation should be reviewed from this perspective, aiming to ensure lower costs associated with investment projects. Key words: Investment projects. Value added tax. Fixed assets. ICMS credits.